Synthesis of silver nanoparticles in an aqueous suspension of graphene oxide sheets and its antimicrobial activity - Das, Manash R.; Sarma, Rupak K.; Saikia, Ratul; Kale, Vinayak S.; Shelke, Manjusha V.; Sengupta, Pinaki (Colloids and Surfaces B-Biointerfaces, 2011)
A solution-based approach to the synthesis of silver (Ag) nanoparticles by chemical reduction of AgNO3 in a graphene oxide (GrO) suspension is demonstrated. X-ray diffraction and transmission electron microscopy indicate that the Ag nanoparticles, of size range 5-25 nm, were decorated on the GrO sheets. The size and shape of the Ag nanoparticles are dependent on the concentration of the AgNO3 solution. Antimicrobial activity of such hybrids materials is investigated against the Gram negative bacteria Escherichia coli and Pseudomonous aeruginosa. The bacterial growth kinetics was monitored in nutrient broth supplemented with the Ag nanoparticle-GrO suspension at different conditions. It was observed that P. aeruginosa is comparatively more sensitive to the Ag nanoparticle-GrO suspension. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial activity; Escherichia coli; graphene oxide; Pseudomonous aeruginosa; Silver nanoparticle

Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2013)
A new Fe3O4-SWCNH nanocomposite was synthesized as an electrode material for supercapacitors. The nanocomposite exhibited a high specific capacitance of 377 F g(-1) and delivered a stable discharge capacitance at a current density of 1 A g(-1) over 1000 cycles between 0 and 1.2 V.

Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode (vol 3, pg 21390, 2013) - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2014)

Synthesis and electrochemistry of pseudocapacitive multilayer fullerenes and MnO2 nanocomposites (vol 2, pg 2152, 2014) - Azhagan, Muniraj Vedi Kuyil; Vaishampayan, Mukta V.; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)

Synthesis and electrochemistry of pseudocapacitive multilayer fullerenes and MnO2 nanocomposites - Azhagan, Muniraj Vedi Kuyil; Vaishampayan, Mukta V.; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Electrode materials with efficient capabilities for ionic and electronic transport are key to high performance supercapacitors. Here, we demonstrate a simple and comparatively low temperature synthesis of functionalized multilayer fullerenes so called carbon nano-onions (CNOs) as the electrode for high performance electrochemical supercapacitors. The exohedral type supercapacitor formed due to nonporous CNOs showed higher specific capacitance than conventional graphitic/mesoporous/activated carbons. Surface redox functionalities of these CNOs add up to significant pseudocapacitance. Further in situ incorporation of MnO2 nanoparticles to these CNOs increased the specific capacitance up to 1207 F g(-1), which is close to the theoretical value of pseudocapacitive MnO2.

Synthesis of N, F and S co-doped graphene quantum dots - Kundu, Sumana; Yadav, Ram Manohar; Narayanan, T. N.; Shelke, Manjusha V.; Vajtai, Robert; Ajayan, Pulickel M.; Pillai, Vijayamohanan K. (Nanoscale, 2015)
Graphene quantum dots (GQDs) are a promising category of materials with remarkable size dependent properties like tunable bandgap and photoluminescence along with the possibility of effective chemical functionalization. Doping of GQDs with heteroatoms is an interesting way of regulating their properties. Herein, we report a facile and scalable one-step synthesis of luminescent GQDs, substitutionally co-doped with N, F and S, of similar to 2 nm average size by a microwave treatment of multi-walled carbon nanotubes in a customized ionic liquid medium. The use of an ionic liquid coupled with the use of a microwave technique enables not only an ultrafast process for the synthesis of co-doped GQDs, but also provides excellent photoluminescence quantum yield (70%), perhaps due to the interaction of defect clusters and dopants.

Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell

Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors - Chaturvedi, Vikash; Usangonvkar, Saurabh; Shelke, Manjusha V. (RSC Advances, 2019)
The remnants of the anaerobic digestion process, `the digestate,' mainly consist of fibrous lignin and cellulose like molecules, as a significant carbon repository along with some other inorganic impurities. The present work demonstrates the potential use of anaerobically treated fruit and vegetable waste (FVW) as a source of porous carbon for supercapacitor electrode materials. This work suggests that the FVW digestate can inherit silicon (Si) and calcium (Ca) based inorganic impurities, which play an essential role as structure directing agents for digestate derived carbon. These contaminants act as hard templates during carbonization to create hierarchical pores and contribute to an enhancement in surface area. Different batches from an anaerobic biogas digester plant are converted to porous carbon and examined as a potential supercapacitor electrode material. A maximum capacitance of 235 F g(-1) is achieved from DDHPC-4kh carbon with a specific surface area of 2502 m(2) g(-1) at a current density of 1 A g(-1) in an acidic aqueous electrolyte. The results are significant in comparison to other bio-sourced precursors studied previously.

Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors (vol 9, pg 36343, 2019) - Chaturvedi, Vikash; Usgaonkar, Saurabh; Shelke, Manjusha V. (RSC Advances, 2020)
Correction for `Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors' by Vikash Chaturvedi et al., RSC Adv., 2019, 9, 36343-36350.